Escherichia Coli K1-colibactin meningitis induces microglial NLRP3/IL-18 exacerbating H3K4me3-synucleinopathy in human inflammatory gut-brain axis - Van Thi Ai Tran; Xiaohui Zhu; Ariunzaya Jamsranjav; Luke P. Lee; Hansang Cho (Communications Biology)
Abstract Escherichia coli K1 (E. coli K1) meningitis early occurs in the gastrointestinal and causes severe damage to the central nervous system, including lifelong neurological complications in survivors. However, the cellular mechanism by which E. coli K1 may cause neuropathies is not well understood due to the lack of relevant human multi-organ models for studying multifaceted systemic inflammation across the gut-brain axis. Here, we reconstruct a multicellular model of the human gut-brain axis to identify the neuropathogenic mechanism driven by E. coli K1-colibactin meningitis. We observed that E. coli K1-genotoxic colibactin induced intestinal and peripheral interleukin 6, causing the blood-brain barrier injury and endothelial inflammation via the p38/p65 pathways. Serpin-E1 from the damaged cerebral endothelia induces reactive astrocytes to release IFN-γ, which reduces microglial phagocytosis of E. coli K1 and exacerbates detrimental neuroinflammation via NLRP3/IL-18 axis. Microglial IL-18 elevates neuronal reactive oxidative stress that worsens DNA double-strand breaks in E. coli K1-infected neurons, leading to H3K4 trimethylation and phosphorylation of alpha-synuclein. Our findings suggest therapeutic strategies for post-bacterial meningitis treatment to potentially prevent the initiation of synucleinopathy.